AN AUTOMATED SYSTEM FOR IOL POWER PREDICTION - Johny, Anitha; K P, Honey; L, Rohini; S, Divya K; M , Sumesh (International Journal of Psychosocial Rehabilitation, 2020)
hen planning for cataract surgery ,to achieve the desired postoperative refraction, the required power of the Intraocular lens(IOL) implant needs to be calculated. Power depends on many factors which are taken from the eye that includes refractive power, media type, actual length and model of lens used. Data Sets are collected using IOL Master 500 which is the most commonly used device in the Hospitals. It has some of the IoL power calculation equations like SRK II, SRK T, Hoffer Q and Holladay. The output power is manually calculated by the doctor. This manual selection can be made easier by an automatic prediction system. To predict this value different machine learning techniques are used. The collected data sets are trained under different machine learning models to obtain best one. From the predictions we find Regression as best model and further analysis is performed by considering RMSE values, P values etc and the power is predicted